Characterization of Isolates of Meloidogyne from Rice-Wheat Production Fields in Nepal - Pokharel, Ramesh R. (The Society of Nematologists, 2007)
Thirty-three isolates of root-knot nematode were recovered from soil samples from rice-wheat fields in Nepal and maintained on rice cv. BR 11. The isolates were characterized using morphology, host range and DNA sequence analyses in order to ascertain their identity. Results indicated phenotypic similarity (juvenile measurements, perennial pattern, host range and gall shape) of the Nepalese isolates with Meloidogyne graminicola, with minor variations. The rice varieties LA 110 and Labelle were susceptible to all of the Nepalese isolates, but differences in the aggressiveness of the isolates were observed. Phylogenetic analyses based on the sequences of partial internal transcribed spacer (ITS) of the rRNA genes indicated that all Nepalese isolates formed a distinct clade with known isolates of M. graminicola with high bootstrap support. Furthermore, two groups were identified within the M. graminicola clade. No correlation between ITS haplotype and aggressiveness or host range was found among the tested isolates.